Effects of Modified Parvalbumin EF-Hand Motifs on Cardiac Myocyte Contractile Function - Asp, Michelle L. (Biophys J, 2016)
Cardiac gene delivery of parvalbumin (Parv), an EF-hand Ca(2+) buffer, has been studied as a therapeutic strategy for diastolic heart failure, in which slow Ca(2+) reuptake is an important contributor. A limitation of wild-type (WT) Parv is the significant trade-off between faster relaxation and blunted contraction amplitude, occurring because WT-Parv sequesters Ca(2+) too early in the cardiac cycle and prematurely truncates sarcomere shortening in the facilitation of rapid relaxation. We recently demonstrated that an E → Q substitution (ParvE101Q) at amino acid 12 of the EF-hand Ca(2+)/Mg(2+) binding loop disrupts bidentate Ca(2+) binding, reducing Ca(2+) affinity by 99-fold and increasing Mg(2+) affinity twofold. ParvE101Q caused faster relaxation and not only preserved contractility, but unexpectedly increased it above untreated myocytes. To gain mechanistic insight into the increased contractility, we focused here on amino acid 12 of the EF-hand motif. We introduced an E → D substitution (ParvE101D) at this site, which converts bidentate Ca(2+) coordination to monodentate coordination. ParvE101D decreased Ca(2+) affinity by 114-fold and increased Mg(2+) affinity 28-fold compared to WT-Parv. ParvE101D increased contraction amplitude compared to both untreated myocytes and myocytes with ParvE101Q, with limited improvement in relaxation. Additionally, ParvE101D increased spontaneous contractions after pacing stress. ParvE101D also increased Ca(2+) transient peak height and was diffusely localized around the Z-line of the sarcomere, suggesting a Ca(2+)-dependent mechanism of enhanced contractility. Sarcoplasmic reticulum Ca(2+) load was not changed with ParvE101D, but postpacing Ca(2+) waves were increased. Together, these data show that inverted Ca(2+)/Mg(2+) binding affinities of ParvE101D increase myocyte contractility through a Ca(2+)-dependent mechanism without altering sarcoplasmic reticulum Ca(2+) load and by increasing unstimulated contractions and Ca(2+) waves. ParvE101D provides mechanistic insight into how changes in the Ca(2+)/Mg(2+) binding affinities of parvalbumin’s EF-hand motif alter function of cardiac myocytes. These data are informative in developing new Ca(2+) buffering strategies for the failing heart.